Electrophysical parameters of the basalt rock of the Kyzyl-Kiy deposit (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
We carried out experimental studies of the electrical properties of basalt rocks in the temperature range from 20°C to 1000°C in air. To measure the electrical conductivity of basalt, a sample was made in the form of a disk 2-5 mm thick and 35 mm in diameter. Electrodes were applied to the end surfaces of the disk by sputtering a thin layer of metal in a vacuum. A round copper metal foil with a diameter of 30 mm was fixed to the surface of the sample using petroleum jelly as an electrode. During the experiments, the optimal size of the basalt sample was established, which turned out to be equal to V=1.48•10-4 m3. It has been shown that increasing the volume of the test sample starting at a temperature of 300°C and above leads to its destruction. This is due to the beginning of CO2 volatilization. Since, under the influence of an electric current, CO2 is concentrated in the middle of the sample under study and after the spontaneous release begins, the destruction of the basalt sample occurs. It has been established that in the temperature range from 450°C to 850°C, the electrical resistivity of basalt rocks changes according to an exponential law. It was revealed that in the temperature range t = 300 – 4500C it evaporates in the form of a mixture of gases SO2, SO3 CO, CO2, Cl2, NH3, while up to a temperature of 3000C the main component of volatile elements is CO2. This process has little effect on the electrical conductivity of the unfired basalt sample. For calcined basalt in the temperature range t=20-4500С its specific resistance takes a constant value, but in the temperature range from 450°С to 1000°С the resistivity of basalt changes according to the exponential law: σ = σ0 • exp(-Ea/KT ). The values of the activation energy of basalt at medium and high temperatures were determined, which turned out to be equal, respectively, E1 = 0.112 eV and E2 = 0.16 eV. Based on the data obtained, it was concluded that the electrical conductivity of basaltic rocks is due to impurity ions and electrons and the presence of a small number of free electrons.
Keywords: basalt; temperature; resistivity; activation energy; volatile gases; electrical conductivity of basalt